(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
To evaluate the significance of Thevetia neriifolia in folk medicine for curing skin infections, an efficacy study was conducted using bacterial (Staphylococcus aureus, Streptococcus pyogenes, Nocardia asteroids, Proteus mirabilis and Pseudomonas aeruginosa) and fungal pathogens (Candida albicans and Trichophyton rubrum) that cause various dermatological disorders. For antimicrobial properties, different fractions of hot extracts of shade dried leaves were assessed by Agar well diffusion method using concentrations ranging from10 mg/50µl/well and compared with reference antibiotics Gentamicin and Fluconazole (25-50µg/well). Of these, petroleum ether fraction was almost ineffective; chloroform fraction showed better efficiency at very low dozes (0.05-0.0125 mg/well) against C. albicans (19.00±1.00) and N. asteroids (14.5±0.71), ethyl acetate fraction was sensitive at higher doses against both fungal cultures T. rubrum (17.67±0.58), C. albicans (15.33±0.58) followed by bacterial strain N. asteroids (15.67±1.52), where as methanol division inhibited colony growth moderately against all the tested organisms (10-13mm). Better DPPH free radical scavenging activity was shown by EA and MT fractions of hot extract with IC50 values 0.72 and 0.81mg/ml respectively. Similarly, cold methanol extract also acted as powerful free radical scavengers of DPPH, super oxide and nitric oxide with low IC50 Values (DPPH-0.46 mg/ml, SOD-0.91 mg/ml, NO-0.88 mg/ml). In conclusion, higher antimicrobial and antioxidant compounds in the leaf add more value to the therapeutic field in drug development for curing many cutaneous bacterial and fungal infections.